2019
DOI: 10.1167/iovs.18-26298
|View full text |Cite
|
Sign up to set email alerts
|

Greater Severity of Glaucomatous Damage in Eyes With Than Without Choroidal Microvasculature Dropout in Open-Angle Glaucoma

Abstract: Citation: Jo YH, Kwon J, Shon K, Jeong D, Kook MS. Greater severity of glaucomatous damage in eyes with than without choroidal microvasculature dropout in open-angle glaucoma. Invest Ophthalmol Vis Sci. 2019;60:901-912. https://doi.org/ 10.1167/iovs.18-26298 PURPOSE.To assess whether open-angle glaucoma (OAG) eyes with choroidal microvasculature dropout (CMvD) have greater severity of glaucomatous damage compared to those eyes without CMvD. METHODS.In this retrospective case-control study, 80 eyes of 80 OAG pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…inferior hemiretinae) of CMvD(+) eyes than in those of CMvD(−) eyes, notwithstanding a similar average RNFLT and VF severity in both groups ( P < 0.05, Table 1 ). These findings are consistent with those of Jo et al, which demonstrated that OAG eyes with a localized CMvD exhibit more severe RNFLT and cpVD loss in the same location compared to those without CMvD despite having similar glaucoma severity 13 . Furthermore, the global pCVD in the β-PPA was significantly lower in CMvD(+) eyes than CMvD(-) eyes in the current series of OAG eyes (Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…inferior hemiretinae) of CMvD(+) eyes than in those of CMvD(−) eyes, notwithstanding a similar average RNFLT and VF severity in both groups ( P < 0.05, Table 1 ). These findings are consistent with those of Jo et al, which demonstrated that OAG eyes with a localized CMvD exhibit more severe RNFLT and cpVD loss in the same location compared to those without CMvD despite having similar glaucoma severity 13 . Furthermore, the global pCVD in the β-PPA was significantly lower in CMvD(+) eyes than CMvD(-) eyes in the current series of OAG eyes (Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although it is unclear why CMvD is frequently found at the inferotemporal parapapillary region, this location is consistent with the macular vulnerability zone in the retina, which corresponds to the zone that is particularly susceptible to glaucomatous damage 12 . In line with this possibility, previous studies have shown that a localized CMvD at the inferior hemiretinae in OAG eyes is associated with glaucomatous RNFL damage in the same hemiretinae, and VF damage in the superior hemifield of eyes 8 , 13 . These earlier findings suggested that the presence of CMvD may play an important role in the pathogenesis of glaucoma, the mechanism of which remains to be further explored.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The structural association between RNFL defect and MvD as shown in Figure 4 may plainly explain (1) why the topography is related to the RNFL defect 9 , 13 , 14 and preconditioned by the presence of βPPA, 1 , 9 , 27 (2) why MvD and glaucomatous damage have a proportional relationship both cross-sectionally 1 6 and longitudinally, 3 , 5 , 7 and (3) why our study group showed such a high prevalence of MvD compared to other studies. The NAION eyes had 100% MvD and 100% PPA, while the eyes with compressive optic neuropathy had MvD in only 34.1% of eyes and PPA in only 68.2% of eyes.…”
Section: Discussionmentioning
confidence: 99%